Metabolic engineering yeast cells for medium-chained biofuel synthesis - Li, Xiang (2015)
Biotechnologies could potentially support renewable fuels production by modifying existing pathways or by creating synthetic routes via metabolic engineering. Recently, metabolic engineering technique has been applied to synthesize biofuels to meet the exploding energy demand and petroleum shortage. In this work, Saccharomyces cerevisiae capable of synthesizing medium-chained hydrocarbons was constructed. The hydroperoxide pathway from almond which consists of lipoxygenase (LOX) and hydroperoxide lyase (HPL), catalyzed linoleic acid to 3(Z)-nonenal as medium-chained biofuel precursor, was introduced into S. cerevisiae wild type, pxa1, pxa2 and pxa1&2 mutants to construct whole-cell based biocatalysts. Then aldehyde decarbonylase (ADC) was introduced to catalyze the 3(Z)-nonenal into octene, which was the final target hydrocarbon. Previous studies have discovered that -oxidation in S. cerevisiae was confined in peroxisomes. Long-chained fatty acids (LCFAs) were first activated in cytoplasm and then transported into peroxisomes for degradation by the ATP binding cassette (ABC) transporter Pxa1/Pxa2. Therefore, the single mutants and double mutant of this transporter were adopted, aiming to retain the absorbed LCFAs in cytoplasm. Proteomics study through LC-MS/MS approach was carried out to implement the investigation of overall protein levels. 31 proteins showed different expression levels among the functional strains WT-9LHP, pxa1-9LHP, pxa2-9LHP, pxa1&2-9LHP. The proteins involved in galactose metabolism, glycolysis, tricarboxylic acid cycle (TCA cycle) and ATP synthesis were notably up-regulated in the strain pxa1&2-9LHP, which suggested the higher activities of metabolism and energy provision. Furthermore, several proteins involved in amino-acid metabolism and protein biosynthesis, which would support the expression of the exogenous genes, were also significantly up-regulated in the same strain. The proteomics study indicated that functional strain pxa1&2-9LHP may display the highest biotransformation efficiency. After the proteomics study, the biotransformation capabilities of the functional strains were determined. Biotransformation using resting cells with linoleic acid added to the culture media was carried out and produced 3(Z)-nonenal was qualified and quantified with gas chromatography-flame ionization detector (GC-FID). The functional pxa1&2-9LHP strain showed the highest yield of up to 1.21 mg/L. The carbon recovery rate was calculated to be 12.1%. The biotransformation results corresponded to our expectations from the proteomics study. This indicated that double disruption of the peroxisomal transporter would influence the flux of absorbed linoleic acid and further help to retain the absorbed linoleic acid in cytoplasm for degradation through the hydroperoxide pathway. ADC introduced into the functional strains was successfully expressed; however, gas chromatography-mass spectrometry (GC-MS) detection proved that the level of the produced octene was non-detectable. In the future, the overall optimization should be carried out, including: 1) the selection of microbial host and culture conditions, changing the expression host into other oleaginous species, Yarrowia lipolytica for instance. 2) the expression conditions of ADC, including structure-based modification to improved enzyme properties, the steric configuration and the kinetics properties. 3) cofactors and byproducts balancing, to make the metabolically engineered microbial host reach a novel systematic balance. The approach described here would potentially contribute to the production of medium-chained biofuel precursors and then biofuels, which is one step further towards the goal of low-cost renewable transportation fuels.